2018
DOI: 10.1016/j.nrl.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Vitamina D y remielinización en la esclerosis múltiple

Abstract: VD seems to play a role in the CNS and our hypothesis is that VD is involved in remyelination. Understanding the basic mechanisms of VD in myelination is necessary to manage multiple sclerosis patients with VD deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 131 publications
0
4
0
Order By: Relevance
“…In the development of MS, CD4 T lymphocytes (or T helper lymphocytes, including Th1, Th2, Th17 subsets) play a crucial role in the activation of myelin-specific Th1 and Th17 cells, which drives the inflammation within the central nervous system [ 36 , 37 ]. Second, MS is characterized by progressive demyelination, vitamin D is deemed to have a role in the myelination and remyelination processes [ 38 41 ], and finally, 80% of MS-associated genes are enriched for VDREs in their promoter region and consequently, and they are regulated by vitamin D [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the development of MS, CD4 T lymphocytes (or T helper lymphocytes, including Th1, Th2, Th17 subsets) play a crucial role in the activation of myelin-specific Th1 and Th17 cells, which drives the inflammation within the central nervous system [ 36 , 37 ]. Second, MS is characterized by progressive demyelination, vitamin D is deemed to have a role in the myelination and remyelination processes [ 38 41 ], and finally, 80% of MS-associated genes are enriched for VDREs in their promoter region and consequently, and they are regulated by vitamin D [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activated microglia may contribute to the immunopathogenesis of MS through several mechanisms that involve an increased secretion of proinflammatory cytokines, chemokines, free radicals, and glutamate [5]. The overexpression of those molecules can provide a hostile microenvironment that limits oligodendrocyte precursor cells (OPCs) migration and differentiation into myelinating oligodendrocytes and leads to ineffective remyelination at the advanced stages of the disease [24].…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…As a result, MS physicians routinely prescribe oral supplements of Vit D3 to increase and maintain Vit D levels in MS patients (Dörr et al, 2020 ). Previous studies suggest that Vit D3 plays a pivotal role in immunomodulatory in MS (Chiuso-Minicucci et al, 2015 ; Mimura et al, 2016 ) and remyelination through stimulating the differentiation of oligodendrocyte progenitor cells (OPC; de la Fuente et al, 2015 ; Matías-Guíu et al, 2018 ). In addition, Wergeland et al ( 2011 ) reported that administration of Vit D3 after 2 weeks of cuprizone (CPZ) withdrawal improved remyelination, and inhibited microglia/macrophage activation in the CPZ mouse model.…”
Section: Introductionmentioning
confidence: 99%